Pulmonary hypertension secondary to Abernethy malformation with left inferior vena cava: a case report and literature review - Xiaoxue Zhang; Mingyu Peng; Ruichen Ren; Wenting Li; Qingyuan Zhao; Chengcheng Qi; Yang Zhang (Frontiers in Medicine)
BackgroundAbernethy malformation is a rare condition in which the portomesenteric blood drains into systemic circulation, bypassing the liver. With advancements in imaging techniques and increased awareness of this malformation, there has been a growing number of reported cases in recent years. We present a case report and literature review in an effort to further the understanding of Abernethy malformation.Case presentationWe report a 21-year-old male presenting with pulmonary hypertension (PH) and right heart enlargement for 7 days. Portal CT angiography (CTA) revealed a vessel communication between the portal vein (PV) and the IVC, located on the left side of the abdominal aorta below the renal vein, and multiple nodular liver lesions (NLL). Finally, Abernethy malformation type II was diagnosed, which is extremely rare due to the absence of polysplenia while co-existing with anomalies of inferior vena cava (AIVC). He was discharged with stable vital signs on symptomatic therapy.ConclusionAbernethy malformation presents with a range of clinical manifestations. It should be considered in patients with unexplained PH.